Driving actin dynamics under the influence of alcohol. - Sordella, R.; Van, A. (Cell, 2006)
The actin cytoskeleton plays a pivotal role in regulating neuronal development and activity, and dysregulation of actin dynamics has been linked to impaired cognitive function. In this issue of Cell Rothenfluh et al. (2006) , and Offenhäuser et al. (2006) show that actin dynamics can also affect the cellular and behavioral responses of flies and mice to alcohol.